Propofol‐induced acute pancreatitis. (10th April 2017) - Csomor, J.; Murínová, I.; Broulíková, K.; Kučerka, O.; Sedloň, P.; Jarošek, J.; Urbánek, P.; Zavoral, M.
Summary: What is known and objective: Drug‐induced acute pancreatitis comprises only 0.5%‐2% of all cases of acute pancreatitis. Propofol is a potentially dangerous drug that can cause acute pancreatitis, but this complication is extremely rare. Case summary: A 57‐year‐old patient developed acute pancreatitis after a planned thyroidectomy. As the common causes of acute pancreatitis were excluded, we believe that the pancreatitis was drug‐induced, in this case by a single dose of propofol administered to the patient during the surgery. What is new and conclusion: We present a rare case of propofol‐induced acute necrotising pancreatitis, which is to the best of our knowledge the first fatal case reported in an adult patient. Abstract : Drug‐induced acute pancreatitis comprises only 0.5‐2% of all cases of acute pancreatitis. Propofol is a potentially dangerous drug that can cause acute pancreatitis, but this complication is extremely rare. We present a very rare case of propofol induced acute necrotising pancreatitis, which is to the best of our knowledge the first fatal case reported in an adult patient.